BF3*OEt2 catalyzed synthesis of spiropyrrolidine frameworks via (3, 5)-oxonium-ene cyclization. (28th September 2022) - Prudhvi Raju, N.; Jagan Mohan Reddy, B.; Rasvan Khan, P.; Aita, Saikiran; Jithender Reddy, G.; Sridhar, B.; Subba Reddy, B.V.
Graphical abstract: Highlights: First report on spiropyrrolidine by Prins cyclization. Catalyst is readily available at low cost. Mild reaction conditions. Short reaction times. Abstract: γ-Hydroxyolefin derived from proline undergoes a smooth ene cyclization with aldehydes to produce the 7-oxa-1-azaspiro[4.5]decane scaffolds in good yields. Whereas the condensation of γ-hydroxyalkene with 2-hydroxybenzaldehyde affords the corresponding tetrahydro-2 H -spiro[pyrano[3, 2- c ]chromene-3, 2′-pyrrolidine derivatives in excellent yields. This is the first report on the ene cyclization of aldehydes with γ-hydroxyalkene derived from the α-amino acid, proline.